TINDAK PIDANA NARKOTIKA TERHADAP ANAK DIBAWAH UMUR - Ozi Saputra; Yusuf Setyadi (JOURNAL OF LAW AND NATION, 2022)
In the juvenile criminal justice system in Indonesia, children as narcotics abusers undergo a criminal justice process. As a vulnerable party in the criminal justice process, even though they are undergoing a judicial process, children must still receive protection. The purpose of this research is to find out the form of protection and what factors are the barriers to legal protection for children as narcotics abusers in the criminal justice system, as a discourse that will be discussed in this study. The method used is normative legal research method, namely reciprocal research between legal norms and social facts. The results of this study indicate that in the perspective of Law No. 35 of 2009 concerning Narcotics, it is not specifically regulated regarding children as perpetrators of narcotics abuse. Through diversion, children who abuse narcotics get protection. The form of diversion of children as narcotics abusers is possible by handing them back to their parents/guardians or participating in education and training and community services.